Percepção de usuários e profissionais envolvidos em curso para pais grávidos oferecido por serviço de saúde suplementar - Nanamura, Márcio H. S. (2017)
The gestational period brings many physical, emotional and psychosocial changes, generating many expectations in the couple and based on that, in different services it was created the course for pregnant women with the intention to solve doubts and humanize the care to pregnant women and in a certain way reduce the excess of technology present in medicine, which ends up distancing, making the process impersonal. However, the benefits of these health education activities are not always described as efficient. The present study aims to evaluate a course already offered by a supplementary health care company, and to discuss a new course approach for pregnant women to be applied in supplementary health, taking advantage of the good things from the course that already exists. In the research were pregnant women and their companions who attended the course and the collaborators who promoted the class, which were in total 35 people - 16 pregnant women; 15 companions and 4 employees. The pregnant women and their companion companions were submitted to a questionnaire before and after the lecture, which asked if some of the main themes related to the pregnancy-puerperal cycle of gestation had been approached in class. There was also a group dynamics when the pregnant women and their companions made engravings to answer motivating questions, reporting the experiences related to situations experienced in the course and expectations regarding childbirth. After the statistical analysis of the data, it was found that for some of the topics covered in the course, such as guidance on gestation, guidance on childbirth, orientation on the type of delivery, learning about the first care with the new-born, knowledge about how there is a significant change of perspective after the course. In relation to the qualitative analysis of the data prevail the feelings involved mainly associated to the fear and the insecurity. We conclude that the course was well evaluated by the participants, however, it could be offered to pregnant women who were in the same phases of gestation (by quarters); It should be included the initial / final evaluation and in relation to the methodology, this could be through group dynamics, where it would be better used and the sharing of knowledge would discourse on the themes